Mechanical and acoustic emission properties of vegetable fiber‐reinforced epoxy composites for percussion instrument drums - Liu, Fanxizi; Wang, Keqin; Lang, Chenhong; Guan, Fuwang; Jiang, Jinhua; Qiu, Yiping (Polymer composites, 2021)
Percussion instrument drums are traditionally made of wood, which is becoming less available as environmental concerns grow. In order to replace wood in percussion instruments, four types of epoxy resin composites reinforced with fabrics of hemp, flax, ramie, and jute, respectively, are fabricated using vacuum assisted resin infusion molding. The tensile and flexural properties of the composites are measured and compared with those of ailanthus wood. The results show that the flexural strengths and moduli of the composites are either better or in between to those of the horizontal and vertical strips of the wood. An acoustic test method is developed to test the acoustic performance of the composites and the wood. The results show that the composites have lower acoustic dynamic moduli, acoustic radiation damping coefficients, sound velocity, and higher acoustic impedance than those of the wood due to their lower flexural moduli and higher specific densities. The shapes of the acoustic spectra for the composites are somewhat similar to those of ailanthus. The acoustic performance comprehensive scores of the four composites are also in between those of the vertical and the horizontal strips of ailanthus. It is possible to match the acoustic performance of ailanthus by increasing the flexural modulus and decreasing the specific density of the composites through reducing the yarn crimp, increasing the fiber volume fraction, and introducing microvoids into the composites. Acoustic spectral performance test of (a) four composite materials and (b) ailanthus. Acoustic properties of natural cellulose fiber reinforced epoxy composites were compared with ailanthus wood for their potential application in musical percussion instrument drums. We found that the acoustic performance of the composites was in between the vertical and horizontal strips of the wood and could be suitable to replace wood in percussion musical instrument if the density and the modulus of the composites can be tailored to mimic the wood.